ANTIOKSIDAN ALAMI SEBAGAI PENGAWET MAKANAN DAN PEMELIHARAAN KESEHATAN TUBUH - Sukardi, Sukardi (Jurnal Bestari, 2001)
Natural antioxidants were isolated from the plants or the rhizomes. Main compounds are phenolics, flavonoids, and isoplavons. Antioxidant activity of the phenolics was determined by the inhibition of autooxidation of linoleac acid in water-alcohol system. Anti-inflamatory activity of the isolated compounds was determined on mouse ears by using a tumour promotere.